Numerical studies of the resistance of concrete keyed joints with rectangular keys in reinforced concrete structures - Demchenko , Oksana; Myshchenko, Mykola (Academic journal Industrial Machine Building Civil Engineering, 2025)
Numerical investigations were carried out on the behavior of keyed joints with rectangular keys in reinforced concrete elements under different failure mechanisms. A two-dimensional nonlinear model was developed in Simulia Abaqus with the concrete damage plasticity approach, accounting for material nonlinearity and contact interaction between joint components. Various failure modes were received, including through-crack formation, key tearing-off, shear failure, and bearing surface crushing. It was investigated how the tensile and compressive strength parameters of concrete affect the bearing capacity of a concrete joint under different types of failure. The specifics of modeling such problems in Simulia Abaqus and the problems of solution convergence were studied.
Keywords: bearing capacity; reinforced concrete keys; deformation model; numerical simulation